Financial Deregulation and Integration in East Asia. - Ito, Takatoshi (National Bureau of Economic Research-East Asia Seminar on Economics., 1996)
The increased mobility and volume of international capital flows is a striking trend in international finance. While countries worldwide have engaged in financial deregulation, nowhere is this pattern more pronounced than in East Asia, where it has affected in unanticipated ways the behavior of exchange rates, interest rates, and capital flows. In these thirteen essays, American and Asian scholars analyze the effects of financial deregulation and integration on East Asian markets. Topics covered include the roles of the United States and Japan in trading with Asian countries, macroeconomic pol.